Effects of queen importation on the genetic diversity of Macaronesian island honey bee populations (Apis mellifera Linneaus 1758) - Muñoz, Irene (2014)
Beekeeping practices such as the importation of non-native honey bee queens may interact with the conservation of honey bee biodiversity. Island honey bee populations are particularly appropriate to test the impact of the introduction of foreign subspecies into their genetic diversity and structure. Here we have used microsatellite markers to evaluate the temporal genetic variation over the last decade in Macaronesian honey bee populations, which have been exposed to different beekeeping strategies regarding queen importation as previously revealed by mitochondrial determination of the evolutionary lineage: a high level on Tenerife and São Miguel and absent or low on La Palma and Madeira. While genetic diversity remained low(from 0.402 to 0.483 in the previous survey and from 0.390 to 0.513 in the current survey), genetic introgression from foreign honey bees was detected on Tenerife and São Miguel based on Bayesian structure analysis. Nevertheless, the existence of endemic honey bee populations deserving conservation on the Macaronesian Islands can still be inferred from the aforementioned analyses.